FAZLURRAHMAN DAN KONSEPSI PENDIDIKAN ISLAM IDEAL - Nurudin Nurudin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2008)
Fazlurrahman in his conception always emphasizes on the understanding of science from the wide meaning and context. The science cover all dimension of life. There is no dichotomy between the secular science and the Islamic one. Accordingly fit can be realized in the concept of Islamic education universally, hence during brief time Islamic education will possibly become competitive compare to the west education. Integrated approach which integrates the "secular science" and Islamic science will probably bears Moslem scholar in the future.